PENINGKATAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS XII MAN KOTA CIMAHI PADA MATERI SIMPANGAN RATA-RATA MENGGUNAKAN MODEL PROBLEM BASED LEARNING - Tira Ivana Febriani; Devi Nurul Yuspriyati (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
The purpose of this study is to find out: (1) The learning activities of students of class XII IIK MAN Kota Cimahi on average inequality material using the Problem Based learning model. (2) Whether the learning outcomes of students of class XII IIK MAN Kota Cimahi average inequality material using  Problem Based Learning can increase. Research is a class action study, this study is conducted in 2 cycles with each cycle consisting of 2 meetings. Before performing class actions are done ¬pre-test  to students, then carried out cycle I and cycle II activities using the Problem Based Learning model. Based on the results of this study shows an increase in student learning outcomes seen from the completion of student learning outcomes. In cycle I there was an increase of 44% then in cycle II there was an increase of 69% in learning outcomes more than 7. This shows that the improvement of student learning outcomes of class XII IIK MAN Kota Cimahi can be improved through the Problem Based Learning model.